Primary systemic amyloidosis presenting as idiopathic inflammatory colitis. (7th October 2011) - Rahman, Nadeem; Toqeer, Muhammad; Hawley, Ian; Weston-Smith, Simon; Whitehead, Mark W; Rademaker, Johan Willem; McWilliams, Eric
Abstract : A 75-year old-female was referred with chest pain. She was fully investigated and it was felt that her symptoms were non-cardiac. Four months later, she was seen in gastroenterology outpatients with bloody diarrhoea and abdominal pain. Colonoscopy demonstrated inflammation up to the splenic flexure and histology confirmed inflammatory colitis. Later, she developed dyspepsia and weight loss. An oesophagogastroduodenoscopy (OGD) showed Helicobacter pylori negative erosive gastritis with a benign duodenal ulcer. Whole body CT scan was normal. Ten months later, she was admitted with dyspnoea due to severe heart failure. The admission ECG had significantly changed, now showing low voltage complexes and repeat echocardiography showed restrictive cardiomyopathy. Specific congo red staining on the biopsy specimens from the previous OGD and colonoscopy confirmed amyloid deposits. Further investigations detected an underlying light chain myeloma causing systemic (AL) amyloidosis. Unfortunately, her condition deteriorated rapidly and she died shortly afterwards.